2012
DOI: 10.1007/s12033-012-9503-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Studies on the Transmission of Indian Cassava Mosaic Virus (ICMV) and Sri Lankan Cassava Mosaic Virus (SLCMV) in Cassava by Bemisia tabaci and Cloning of ICMV and SLCMV Replicase Gene from Cassava

Abstract: Cassava mosaic disease, caused by cassava mosaic geminiviruses are transmitted by Bemisia tabaci. The B. tabaci adults from colonies reared on virus free cassava plant produced from apical meristem culture was studied to determine their ability to transmit Indian cassava mosaic virus (ICMV) and Sri Lankan cassava mosaic virus (SLCMV) from cassava to cassava. Virus free plants were confirmed by polymerase chain reaction (PCR) using geminivirus degenerate primers. The virus acquisition access period (AAP) of 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…SLCMV diagnosis was carried out using specific primers based on the AC1 ( replicase ) gene of SLCMV reported by Duraisamy et al . [12]. Thermal cycling consisted of an initial denaturation at 94°C for 5 minutes, followed by 40 cycles of 2 minutes at 94°C, annealing at 55°C for 30 seconds, 72°C for 1 minute, followed by a final extension of 5 minutes at 72°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SLCMV diagnosis was carried out using specific primers based on the AC1 ( replicase ) gene of SLCMV reported by Duraisamy et al . [12]. Thermal cycling consisted of an initial denaturation at 94°C for 5 minutes, followed by 40 cycles of 2 minutes at 94°C, annealing at 55°C for 30 seconds, 72°C for 1 minute, followed by a final extension of 5 minutes at 72°C.…”
Section: Methodsmentioning
confidence: 99%
“…The recent report of SLCMV in Cambodia expands on previous identifications in Sri Lanka and India [1, 9–11]. Like other CMGs, SLCMV is transmitted by the whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), and through the movement of infected planting materials [12]. With ACMV, plants grown from infected cuttings are more seriously affected than those infected by the whitefly vector [13].…”
Section: Introductionmentioning
confidence: 98%
“…Among all treatments used, highest mean shoot number (58.68±6.57) and number of shoots per explants (129) were obtained on MS medium supplemented with 0.5 mg/l BAP + 0.4 mg/l GA3. Duraisamy et al (2012) also reported that maximum mean number of shoots per explant (6.3±0.09) was obtained using MS medium supplemented with 0.02 mg/l GA3 + 0.1 mg/l BAP on apical meristem cultures of cassava. Tsgaw and Feyisaa (2014) obtained the maximum mean number of shoots per explant (7.2) of P. edulis on MS medium supplemented with 1.0 mg/l KIN + 0.1 mg/l NAA.…”
Section: Shoot Multiplicationmentioning
confidence: 90%
“…Several molecular and serology-based methods have been employed for the detection of CMBs such as PCR [ 20 ], multiplex PCR [ 21 ], real-time PCR [ 22 ], immunosorbent electromicroscopy [ 23 ], double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) [ 24 ] and triple antibody sandwich-ELISA (TAS-ELISA) [ 25 ]. For SLCMV, methods such as PCR [ 26 28 ], multiplex PCR [ 29 , 30 ], rolling circle amplification (RCA) [ 12 ] and plate-trapped antigen-ELISA (PTA-ELISA) [ 15 ] have been described. Although molecular-based methods are known to be more sensitive, ELISA is generally more suitable for routine and large-scale CMD screening, due to its simplicity, high throughput and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%